2023
DOI: 10.3390/coatings13050958
|View full text |Cite
|
Sign up to set email alerts
|

Joining Technologies for Aluminium Castings—A Review

Abstract: Aluminium castings have been widely used in many industries, including automotive, aerospace, telecommunication, construction, consumer products, etc., due to their lightweight, good electric and thermal conductivity, and electromagnetic interference/radio frequency interference (EMI/RFI) shielding properties. The main applications of aluminium castings are in automotive industry. For lighweighting purposes, more and more aluminium castings are used in the automotive vehicle structures to reduce weight, improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 199 publications
(291 reference statements)
0
1
0
Order By: Relevance
“…Al castings from various processes possess different gas content, surface finish, and mechanical properties, causing variations in joinability by fusion welding and mechanical joining [587].…”
Section: Vaporizing Foil Actuator Welding (Vfaw)mentioning
confidence: 99%
See 3 more Smart Citations
“…Al castings from various processes possess different gas content, surface finish, and mechanical properties, causing variations in joinability by fusion welding and mechanical joining [587].…”
Section: Vaporizing Foil Actuator Welding (Vfaw)mentioning
confidence: 99%
“…The same grade of castings obtained from different casting processes can differ in their gas content and joinability. Castings made by high-quality high-pressure die casting (HPDC), squeeze casting, and semi-solid metal SSM casting possess a much lower gas content [587].…”
Section: Vaporizing Foil Actuator Welding (Vfaw)mentioning
confidence: 99%
See 2 more Smart Citations
“…The 1100 alloy is a pure aluminum alloy with high specific strength, high fracture toughness, excellent thermal conductivity, and strong chemical corrosion resistance and weathering resistance. It has become one of the most versatile, cost-effective, and attractive metal materials being widely used in different industrial fields [ 1 , 2 ]. With the advocacy for global energy conservation and emission reduction, research on the corrosion performance of designed aluminum parts has found that the corrosion rate of aluminum alloys under acidic condensation conditions is much lower than that of certain steel grades [ 3 ].…”
Section: Introductionmentioning
confidence: 99%